Comparable cognitive impairment was detected in MACS and CS and alleviated after remission of hypercortisolism in MACS - Liu, Mengsi; Zhao, Wenji; Zhang, Wei; Tian, Zhaoyang; Zhang, Zhou; Lou, Yuan; Zhang, Ziwei; Yang, Fan; Zhu, Dalong; Li, Ping (Frontiers in Endocrinology, 2024)
Context: Few studies have directly compared the cognitive characteristics of patients with mild autonomous cortisol secretion (MACS) and Cushing's syndrome (CS). The effect of surgical or conservative treatment on cognitive function in patients with MACS is still unclear.Objective: To compare the differences in cognitive function between patients with MACS and CS and evaluate the effect of surgery or conservative treatment on cognitive function.We prospectively recruited 59 patients with nonfunctional adrenal adenoma (NFA), 36 patients with MACS, and 20 patients with adrenal CS who completed the global cognition and cognitive subdomains assessments. Seventeen MACS patients were re-evaluated for cognitive function after a 12-month follow-up period; of these, eleven underwent laparoscopic adrenalectomy and six received conservative treatment.Results: Patients with MACS and CS performed worse in the global cognition and multiple cognitive domains than those with NFA (all P<0.05). No statistical difference was found in cognitive functions between patients with MACS and CS. Logistic regression analysis showed that patients with MACS (odds ratio [OR]=3.738, 95% confidence intervals [CI]: 1.329-10.515, P=0.012) and CS (OR=6.026, 95% CI: 1.411-25.730, P=0.015) were associated with an increased risk of immediate memory impairment. Visuospatial/constructional, immediate and delayed memory scores of MACS patients were significantly improved at 12 months compared with pre-operation in the surgical treatment group (all P<0.05), whereas there was no improvement in the conservative treatment group.: Patients with MACS have comparable cognitive impairment as patients with CS. Cognitive function was partially improved in patients with MACS after adrenalectomy. The current data support the inclusion of cognitive function assessment in the clinical management of patients with MACS.